Age and comorbidities deeply impact on clinical outcome of patients with myelodysplastic syndromes. Issue 8 (August 2015) - Balleari, E.; Salvetti, C.; Del Corso, L.; Filiberti, R.; Bacigalupo, A.; Bellodi, A.; Beltrami, G.; Bergamaschi, M.; Berisso, G.; Calzamiglia, T.; Carella, A.M.; Cavalleri, M.; et al.
Highlights We examine the effects of age and comorbidity in a real-life series of MDS patients. Both age and comorbidities exert a significant, independent impact on clinical outcome. The role of comorbidity in predicting outcome is best described by the MDS-CI score system. The impact of MDS-CI on outcome has particular relevance in lower-risk MDS patients.